Spectrophotometric Method for the Determination of Oxaliplatin in Pure and Dosage Forms - G. Srinubabu; D. Pundarika Rao; L. Sridhar; J. V. L. N. Seshagiri Rao (E-Journal of Chemistry)
A simple and reproducible spectrophotometric method has been developed for the estimation of Oxaliplatin in pure and dosage forms. The method is based on the reaction of the drug with 1, 10 Phenanthroline in presence of ferric chloride, which forms a blood red colored complex exhibiting maximum absorption at 520 nm.